THE INFLUENCE OF MOTIVATION, COMPETENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Nandrang, Rosdiana; Hasanuddin, Bakri; Mahardiana, Lina (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
The purpose of this study was to test and explain empirically (1) Motivation, competence and work discipline have a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (2) Motivation has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (3) Competence has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (4) Work discipline has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency. The type of research used in this study is causality research. Hypothesis testing using Multiple Linear Regression Analysis with a sample of 64 respondents consisting of 40 civil servants and 24 non-civil servants. The results of the analysis show that (1) Motivation, competence and work discipline have a significant effect on employee performance at the Staffing Agency and Regional Human Resources Development of Tojo Una-Una Regency (2) Motivation has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (3) Competence has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (4) Work discipline has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency.